A process for participatory co-design of agroecological Transition pathways at the landscape and food system levels: a process for the articulation of action-research activities and lessons learned from early implementation - Frija, Aymen; Alary, Veronique; M'hamed, Hatem Cheikh; Rudiger, Udo; Idoudi, Zied; Bahri, Haithem; Ajmi, Larbi; Rekik, Mourad; Ouerghemmi, Hassen; Shiri, Zahra (International Center for Agricultural Research in the Dry Areas, 2023)
Many questions and debates are being undertaken in the literature about the “context-specific transition pathways of agroecological transformations and their related conceptual, political, institutional, social, and other challenges and opportunities. Pilot projects for Agricultural Research for Development (AR4D) are key areas where these questions and related assumptions can be tested, piloted, and reported for better lessons and future conceptualization. In this paper, we present the experience of the One CGIAR Initiative on Agroecology transformation for food, land and water systems, which adopted a transdisciplinary, participatory, and action-oriented approach aimed at enhancing food system resilience, equity, and sustainability. Even though the theory of change (ToC) of this initiative was quite clear and robust, its application on the ground, in seven countries, faced a strong challenge of contextualization, which then guided further adjustments of this ToC to better match local expectations thus leading to locally co-identified (co-designed) transition pathways which are the most relevant to local socioecological systems as well as to stakeholders’ preferences and objectives. The paper presents some progress of the initiative implementation from Tunisia case studies thus highlighting a realistic approach (suite of activities), refined with national partners and local communities, for participatory co-design of “Agroecological Transition Pathways” at the living landscape (ALL) and food system levels. The identified (realistic) approach is composed of 10 key steps staring from 1) clearly defining the geographical and conceptual frontiers and intersections between living labs, innovation systems, production system, value chains, socioecological systems, etc. which will then support the clarification and identification of action areas and levels of operation of the ongoing program, 2) Stakeholders’ mapping at different levels with identification of synergies and divergences amongst them, 3) Initial engagement activities of a number of key stakeholders in the living landscape with consolidation of a minimum level of trust amongst them, 4) predefine some "actionable" drivers of territorial change / development, 5) Sharing and validating, among key ALL members, an understanding of the context and of the purpose of the “vision-to-action” process which the project is adopting to design the agroecological transition pathway in the landscape, 6) Developing a shared vision for a desirable future amongst different ALL stakeholders and articulating this vision with the AE principles (by the support of experts and planning agents) through co-validation and participation, 7) Identifying the ALL theory of change and the context (system-) specific Agroecology transition pathways in the living landscape; 8) Identify behavioral change needed to progress on the co-designed transition pathway, 9) Identify behavioral drivers that hinder or support this behavior changes; and finally 10) identify the strategic actions to achieve the behavior changes thus leading to the full, or partial, implementation of the agroecological transition pathways. A year of implementation in semi-arid Tunisia (mostly for steps 1 to 7) thought us quite few lessons: while visioning, engagement, and planning for agroecology were relatively manageable and effective at the community levels, stakeholder engagement for the establishment of agroecological transition pathways at the food system level still faces contextual, conceptual and practical challenges, such as representativeness, conflictual objectives of food system actors and different interests and self-motivations, or even lack of public engagement for facilitation. Furthermore, the landscape approach can be relevant for tailoring a mid-range theory for the transformation of food systems, but the implementation of such a mid-range theory can only be effective if we operate into a complexity-aware and adaptive program framework. Thirdly, facilitation and engagement of food system actors can lead to more conducive environments for the co-design of transition pathways that are well-appropriated by most actors, but the lack of good and neutral facilitators, as well as seed funds for public facilitation are major constraints. Collective learning and consolidation of social capital and collective cognitive capacities of food system actors are key elements leading to “intermediary outcomes” such as sustainable cooperation, partnership, etc., which can then lead to food system transformation. This communication occurred during the ‘sustainable agroecology: governance, practices, potentials, and tensions in a comparative perspective’ workshop in Kassel, Germany, as part of the “Agriculture, Ecology and Societies program” initiative and the DAAD-funded Global Partnership Network of University of Kassel, as well as the DAAD-funded AURORA (Sustainable Agriculture and social-ecological systems approaches in higher education in the MENA region) project, which aims to map sustainable agroecology in diverse social-ecological, historical and geo-political contexts (University of Kassel – 17-18 July 2023).